Strategi Akselerasi Hafalan Al-qur'an Melalui Manajemen Perencanaan Program Tahfidz di Pesantren Modern Darojatul Ashfad - Pupy Endah Sariwulan (Perkumpulan Peneliti dan Pegiat Literasi, 2026)
This study examines the management of tahfidz program planning to accelerate the memorization of students at the Darojatul Ashfad Bekasi Modern Islamic Boarding School. The background arises from the need for a systematic, adaptive, and measurable tahfidz program, so that the memorization process can be more consistent and effective. The research aims to analyze how tahfidz program planning is formulated, implemented, and evaluated as a memorization acceleration strategy. The methods used qualitatively with a case study approach, involving observation, in-depth interviews, and documentation, were analyzed thematically. The results show that planning that adjusts the memorization target to the initial ability of the students, regulates the balance between new memorization and muraja'ah, and is supported by a data-based monitoring and evaluation system, improves the consistency and speed of memorization, with the average daily achievement increasing significantly. These findings confirm that the acceleration of memorization is not just the result of learning intensity, but an adaptive and integrated planning management product. The research provides a practical contribution in the form of a tahfidz planning management model based on memorization acceleration that can be used as a reference for modern pesantren managers to strengthen the effectiveness and quality of tahfidz programs, as well as support the development of contemporary Islamic education management.